会话中的演绎与角色扮演 ：从会话分析的角度探究其运作模式 = Enactment and role-playing in conversation : a study of the operations through conversation analysis - 林丽惠 Lim, Li Hui (2016)
本文将探讨的是一个在日常会话中常用的会话模式。这个模式在本文的研究里将暂以“演绎”为名。在这样的过程中，一个谈话者会开始扮演谈话参与者们共同拟定的场景中的一个角色。当他完成自己的话轮之后，听话人便会在其话轮或之前的话轮里没有进一步阐述所拟定的场景的情况下，使用与第一个说话人相同的方式，扮演场景中相同或不同角色的方式来进行自己的话轮，以回应第一个说话人并延续他所开始叙述的场景或情节。谈话参与者们准确地揣摩和延续演绎的场景，说明他们即使没有互相告知演绎场景的内容，却仍可以对其有充分的理解。本文从会话分析的角度，着重于对演绎过程中的行为和运作模式给予描述，也会探讨三种不同的预设演绎场景的方式。这是因为场景的预设是演绎得以进行的先决因素。本文也会尝试分析谈话参与者在会话中采用演绎，而选择不将其所呈现的主题和观点直言的目的。这同时也是作为演绎的功能所在。This article examines a commonly used practice in daily conversation, tentatively termed “enactment” for this study. This practice is observable when a speaker acts out the role of a character in a specific and constructed scenario intended to be mentioned in his turn of speech. The other participants of the conversation will follow suit subsequently as a response to as well as continuation of the enactment started by playing the role of either the same or another character of that scenario the first speaker had during his turn. The point worth mentioning is that all participants of the conversation do not verbally communicate information of the scenario that is being constructed, yet they are able to display understanding of the unsaid through accurate interpretation and continuation of the scenario which the first speaker has started. Using conversation analysis, this article focuses on describing the actions and operations involved during an enactment. The various ways of presetting the scenario to be used by the participants as a prerequisite for the enactment will also be discussed. This article will then attempt to provide an account for participants to adopt this practice instead of telling the literal meaning of the theme and idea behind the enactment, which simultaneously serves as the function of the enactment.